STUDI INTERTEKSTUALITAS TERHADAP ROMA 8:18-23 - Juppa Haloho (Jurnal Amanat Agung, 2020)
Abstract: As an environmental mantra, Romans 8:18-23 has become one of the main pillars of the Christian ecotheology that gives mandate to Christians to take care of environment. Through this text, ecological crisis can be read not empirically but theologically. The hermeneutical issue of the text is that interpreters do not yet agree about the background of Paul’s argument. In the midst of the variety of interpreters’ suggestions of Paul’s background in Romans 8:18-23, intertextuality approach proposes Isaiah 24:1-7 as an allusion that Paul intentionally alluded to in Romans 8:18-23. Intertextuality approach proves that Isaiah 24:1-7 has some connections with Romans 8:18-23. In writing Romans 8:18-23, Paul had read Isaiah 24:1-7 figuratively in the light of Christ. Thus, restoring the context and theological message of Isaiah 24:1-7 illuminates the reading of Romans 8:18-23. Likewise, understanding why Paul used Isaiah 24:1-7 in Romans 8:18-23 helps readers read Isaiah 24:1-7. Keywords: ecotheology, intertextuality, figural reading, Romans 8 Abstrak: Roma 8:18-23 sebagai environmental mantra merupakan salah satu pilar utama ekoteologi Kristen yang memberikan mandat kepada orang Kristen untuk memperhatikan lingkungan. Melalui teks ini, krisis ekologis dapat dipahami bukan secara empiris melainkan secara teologis. Sekalipun demikian, para penafsir masih belum sependapat mengenai latar pemikiran Paulus dalam Roma 8:18-23. Di tengah beragamnya usulan para penafsir atas latar pemikiran Paulus dalam Roma 8:18-23, pendekatan intertekstualitas mengusulkan Yesaya 24:1-7 sebagai alusi yang sengaja disinggung Paulus dalam Roma 8:18-23. Pendekatan intertekstualitas membuktikan keterkaitan Yesaya 24:1-7 dengan Roma 8:18-23. Dalam menulis Roma 8:18-23, Paulus telah membaca Yesaya 24:1-7 secara figural dalam terang Kristus. Dengan demikian, pemulihan konteks dan pesan teologis Yesaya 24:1-7 menerangi pembacaan Roma 8:18-23. Demikian pula, pemahaman mengapa Paulus menggunakan Yesaya 24:1-7 dalam Roma 8:18-23 menolong pembaca memahami Yesaya 24:1-7. Kata Kunci: ekoteologi, intertekstualitas, pembacaan figural, Roma 8 .